Fabrication of Hydrogel Particles of Defined Shapes Using Superhydrophobic-Hydrophilic Micropatterns - Neto, Ana I.
High-throughput fabrication of freestanding hydrogel particles with defined geometry and size for 3D cell culture, cell screenings, and modular tissue engineering is reported. The method employs discontinuous dewetting using superhydrophobic-hydrophilic micropatterns.